A Pilot Clinical Study on Post-Operative Recurrence Provides Biological Clues for a Role of Candida Yeasts and Fluconazole in Crohn’s Disease - Boualem Sendid; Nicolas Salvetat; Helène Sarter; Severine Loridant; Catherine Cunisse; Nadine François; Rachid Aijjou; Patrick Gelé; Jordan Leroy; Dominique Deplanque; Samir Jawhara; Dinah Weissmann; et al. (Journal of Fungi, 2021)
Background and aims: This study prompted by growing evidence of the relationship between the yeast Candida albicans and Crohn’s disease (CD) was intended to assess the effect of a 6-month course of the antifungal fluconazole (FCZ) on post-operative recurrence of CD. Methods: Mycological samples (mouth swabs and stools) and serum samples were collected from 28 CD patients randomized to receive either FCZ (n = 14) or placebo (n = 14) before surgical resection. Serological analysis focused on levels of calprotectin, anti-glycan antibodies, and antibody markers of C. albicans pathogenic transition. Levels of galectin-3 and mannose binding lectin (MBL) involved in C. albicans sensing and inflammation were also measured. Results: 1, 2, 3, and 6 months after surgery, endoscopy revealed recurrence in 5/12 (41.7%) patients in the FCZ group and 5/9 (55.6%) in the placebo group, the small cohort preventing any clinical conclusions. In both groups, surgery was followed by a marked decrease in C. albicans colonization and biomarkers of C. albicans pathogenic transition decreased to non-significant levels. Anti-glycan antibodies also decreased but remained significant for CD. Galectin-3 and calprotectin also decreased. Conversely, MBL levels, which inversely correlated with anti-C. albicans antibodies before surgery, remained stable. Building biostatistical multivariate models to analyze he changes in antibody and lectin levels revealed a significant relationship between C. albicans and CD. Conclusion: Several combinations of biomarkers of adaptive and innate immunity targeting C. albicans were predictive of CD recurrence after surgery, with area under the curves (AUCs) as high as 0.86. FCZ had a positive effect on biomarkers evolution. ClinicalTrials.gov ID: NCT02997059, 19 December 2016. University Hospital Lille, Ministry of Health, France. Effect of Fluconazole on the Levels of Anti-Saccharomyces cerevisiae Antibodies (ASCA) After Surgical Resection for Crohn’s Disease. Multicenter, Randomized, and Controlled in Two Parallel Groups Versus Placebo.